Cyber Counseling Sebagai Metode Meningkatkan Layanan Bimbingan Konseling di Sekolah - Tambunan, May Dea Citra; Tanjung, Egi Pratama Putra; Thohir, Ulfa Fadhillah; Manurung, Afwan Syahril (Effect : Jurnal Kajian Konseling, 2025)
Internet users are growing rapidly due to advances in information and communication technology Almost all people in the world use the internet in their daily lives. The increasing development of technology also influences the provision of guidance and counseling services, especially in schools. In this era of globalization, online counseling or cyber counseling services are really needed by counselorsor counseling guidance teachers because they can provide services without being limited by distance and time. This research aims to discuss the application of cyber counseling in schools. This research uses a literature review method or literature study in the form of journal articles. The research results show that cyber counseling services are considered effective because they can make it easy for counselors and students to carry out counseling that is not limited by distance and time. Several methods are used to carryout online counseling, including: via email, Facebook, asynchronous chat, Riliv application, video conference, cellphone and website. Counseling guidance teachers and counselors are expected to continue to improve their abilities in using information and communication technology.